ENCHANCEMENT OPERATION SYSTEM MODEL MANAGING LOCAL RESOURCES BASED ENVIRONMENT TOWARDS SUSTAINABLE DEVELOPMENT - Triono Eddy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This paper discussed at exploring an approriate model in managing environment that may accomodate and optimize local resource, such as human resource and natural resources.